Successful Management of a Cystic Lesion Which Had Been Caused by Menstrual Blood Above the Dehiscence of Cesarean Incision Scar: Case Report - Uğur Keskin; Fahri Burçin Fıratlıgil; Mustafa Ulubay; Ulaş Fidan; Rıza Efendi Karaca; Ali Ergün (Gynecology Obstetrics & Reproductive Medicine)
Cesarean scar dehicence has the incidence of 1.2% after base transverse incisions. Beside causing a situation increasing morbidity and mortility for baby and mother and needing acute intervention in antenatal or intrapartum period by causing uterine rupture, it is an important complication that can cause sudden bleeding, infection and even uterine fistules in postpartum period. In our case, we will mention about the successful management of cyst caused by menstrual blood that develops dehiscence of cesarean scar.